Epstein–Barr Virus Infection of Oral Squamous Cells - Chukkris Heawchaiyaphum; Hisashi Iizasa; Tipaya Ekalaksananan; Ati Burassakarn; Tohru Kiyono; Yuichi Kanehiro; Hironori Yoshiyama; Chamsai Pientong (Microorganisms, 2020)
The Epstein−Barr virus (EBV) is a human herpesvirus associated with various cancers. The number of reports that describe infection of EBV in oral squamous carcinoma cells is increasing. However, there is no available in vitro model to study the possible role of EBV in the development of oral squamous cell carcinoma. Herein, we report establishment of a latent EBV infection of well-differentiated HSC1 cells and poorly differentiated SCC25 cells. Viral copy numbers per cell in EBV-infected HSC1 and SCC25 cells are 2 and 5, respectively. Although the EBV copy number was small, spontaneous viral replication was observed in EBV-infected HSC1 cells. Contrarily, infectious viral production was not observed in EBV-infected SCC25 cells, despite containing larger number of EBV genomes. Chemical activation of cells induced expression of viral lytic BZLF1 gene in EBV-infected HSC1 cells, but not in EBV-infected SCC25 cells. EBV infection activated proliferation and migration of HSC1 cells. However, EBV-infection activated migration but not proliferation in SCC25 cells. In conclusion, EBV can infect squamous cells and establish latent infection, but promotion of cell proliferation and of lytic EBV replication may vary depending on stages of cell differentiation. Our model can be used to study the role of EBV in the development of EBV-associated oral squamous cell carcinoma.